High CNT content composites with CNT bucky paper and epoxy resin matrix : impregnation behaviour, composite production and characterization - Lopes, P. E. (2010)
This work provides information on the characterization of carbon nanotube (CNT) skeletons, or Buckypapers, using contact angle and thermogravimetric analysis (TGA) measurements. The preparation of composites using these CNT skeletons and an epoxy resin by impregnation in vacuum and cure in two moulds with different release surfaces is described. Preliminary results for the mechanical performance of the produced composites using mini-tensile test specimens and their characterization by TGA, dynamic mechanical thermal analysis (DMTA) and scanning electron microscopy (SEM) is also presented.